Comparative analysis of filterability behavior of B30 and B40 biodiesel blends on various porosity and dimension of fuel filter - Yogi Pramudito; Nur Allif Fathurrahman; Ahmad Syihan Auzani; Cahyo Setyo Wibowo; Riesta Anggarani; Ariana Soemanto; Bambang Sugiarto (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
This report is focused on comparative analysis of the impact of using biodiesel blends containing more than 30% biodiesel in diesel engine filtration systems. The objective of this study is to support the sustainability of the mandatory biodiesel utilization program by more than 30%. To evaluate filterability behavior of high-percentage biodiesel blends, namely B30 and B40 (30 and 40%-vol biodiesel on diesel fuel), the study employed the ASTM D 2068 Filter Blocking Tendency (FBT). After filter rig test, fuel filter pressure was also evaluated using the JIS 1617 standard method. It is important to note that fuel filter plays an important role in removing contaminants from fuel, and, hence, the effect of the difference in filter porosity needs to be observed with pressure difference across fuel filter monitored at the flow rate (0.03 m3/h and fuel temperature (15 ⁰C and 25 ⁰C). Furthermore, the effect of changes in temperature and surface morphology on the characteristics of filter was observed in this study. Based on FBT analysis, a polynomial regression (R2 > 0.98) was used to describe the relationship between FBT value and the effect of biodiesel blends on filterability. It was concluded that the temperature, monoglyceride content, and FAME concentration in the diesel fuel influenced their FBT. However, the rise in waxy particles at 15oC (near Cloud Point) could result in a more significant average pressure drop than at 25⁰C (ambient temperature). It was also found that a higher biodiesel mixture potentially results in a higher-pressure difference due to the lower fuel temperature and the formation of waxy contaminants that can clog filter.